2013
DOI: 10.1007/s11629-013-2667-8
|View full text |Cite
|
Sign up to set email alerts
|

Implications of climate change on streamflow of a snow-fed river system of the Northwest Himalaya

Abstract: Air temperature and snow cover variability are sensitive indicators of climate change. This study was undertaken to forecast and quantify the potential streamflow response to climate change in the Jhelum River basin. The implications of air temperature trends (+0.11°C/decade) reported for the entire north-west Himalaya for past century and the regional warming (+0.7°C/decade) trends of three observatories analyzed between last two decades were used for future projection of snow cover depletion and stream flow.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 46 publications
(51 reference statements)
0
12
0
Order By: Relevance
“…Discharge of these rivers is mainly contributed by the snow-glacial melt during spring and summer season (Sharma et al, 2013), thus snow cover area (SCA) variation influences the sustainability of millions of people in the Himalayan region (Barnett et al, 2005). Snowmelt contributes ~50% in the annual runoff budget in the western Himalaya (Indus, Sutlej) whereas central and eastern Himalaya catchments receive more than 80% and less than 20% of their annual runoff from rainfall and snowmelt, respectively (except the large Tsangpo/Brahmaputra catchment which receives ~34% of its annual discharge from snowmelt) (Bookhagen and Burbank, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Discharge of these rivers is mainly contributed by the snow-glacial melt during spring and summer season (Sharma et al, 2013), thus snow cover area (SCA) variation influences the sustainability of millions of people in the Himalayan region (Barnett et al, 2005). Snowmelt contributes ~50% in the annual runoff budget in the western Himalaya (Indus, Sutlej) whereas central and eastern Himalaya catchments receive more than 80% and less than 20% of their annual runoff from rainfall and snowmelt, respectively (except the large Tsangpo/Brahmaputra catchment which receives ~34% of its annual discharge from snowmelt) (Bookhagen and Burbank, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Sharma et al (2013) reported that north-western Himalayas are the source of major perennial rivers such as Indus, Jhelum, Satluj, Ravi and Chenab as the discharge of these rivers is mainly contributed by the snow-glacial melt. Thus, it also becomes crucial to analyze the sensitivity of river discharge to SCA.…”
Section: Introductionmentioning
confidence: 99%
“…While this approach compensates for data scarcity in remote areas, it results in snowmelt being unconstrained by the depth of snow. When applied in climate change studies, future snow depletion curves are projected based on temperature [50,89,[139][140][141], but disregard the influence of precipitation-temperature relationships on snowpack formation which has obvious limitations to represent snowmelt water availability under future climate change conditions [120]. The contribution of ice melt from glaciers to total runoff was accounted for in 59% of the applications but less than 18% modelled the mass balance of glaciers [2,51,79,85,92,94,115,130,142,143].…”
Section: Snow and Ice Hydrologymentioning
confidence: 99%
“…Similarly, the land use/land cover inputs generally used are global products derived from satellites such as Landsat [94,113,161], MODIS [107] and IRS-P6 [110,118] that, despite their acceptable spatial resolution, are only available for recent years. Furthermore, the differential illumination caused by the rugged relief can cause imperfect land cover classifications; in fact, some studies explicitly describe the topographic corrections made to obtain a normalised reflectance [78,139]. Specifically for snow cover, MODIS satellite products are the most used [89,94,97,141], sometimes combined with finer resolution Landsat products of fractional snow cover [80,95,128,138].…”
Section: Landscape Datamentioning
confidence: 99%
“…Most of the research to date in the Jhelum and Upper Indus Basin have utilized a few GCMs' under SRES scenarios for climate change impact studies [16][17][18][19][20][21][22]. The SRES scenarios exaggerate resource accessibility and are unlikely on upcoming production outputs from fossil fuels [23].…”
Section: Introductionmentioning
confidence: 99%